L’acceptation de la voiture électrique : un agent transformateur des pratiques socio-domestiques - Lénaïc Poupon; Chrystèle Philipps-Bertin; Marc-Éric Bobillier Chaumon; Nikos Kalampalikis (Activités)
The study of the acceptance of the electric car (EC), show how this technical artefact transforms the domestic activities in a real use context. Data from individual explicit interviews with electric car drivers/owners (n =9) show that the specificities of EC are going to lead the drivers to rethink their driving practices and the regulation of their activity system. To cope with its limited autonomy, they develop strategies such as planning activities and eco-driving behaviors. Besides, drivers are going to increase their vigilance in response to the perception of the dangerousness of the engine noise absence. These adjustments will be part of the instrumental genesis of the electric car and of its appropriation. The rules regulating household trips are going to evolve, as well as those regulating relationships with social others (entourage, road users, automobile professionals).